2022
DOI: 10.1155/2022/4485365
|View full text |Cite
|
Sign up to set email alerts
|

Slime-Groove Drag Reduction Characteristics and Mechanism of Marine Biomimetic Surface

Abstract: With the development of science and technology, energy consumption and demand continue to increase, and energy conservation and consumption reduction have become the primary issue facing the world. Improving the energy efficiency of ships not only helps reduce fuel consumption but also reduces carbon dioxide emissions, which is an important guarantee for the green development of the ocean and the maintenance of ecological balance. Through natural selection and adaptation to the environment after evolution, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…Studies show that the non-Newtonian mucus layer acts as a buffer between the solid fish surface and the surrounding water, effectively creating a slip condition between the fish and the water 153,154 . This is hypothesized to reduce shear at the boundary layer, thus decreasing skin-friction drag 155 (Fig. 4a) 156,157 .…”
Section: Aquatic Bio-inspired Flow Controlmentioning
confidence: 99%
“…Studies show that the non-Newtonian mucus layer acts as a buffer between the solid fish surface and the surrounding water, effectively creating a slip condition between the fish and the water 153,154 . This is hypothesized to reduce shear at the boundary layer, thus decreasing skin-friction drag 155 (Fig. 4a) 156,157 .…”
Section: Aquatic Bio-inspired Flow Controlmentioning
confidence: 99%
“…As a result, the hydrogel or epidermal mucus secreted by fish can be considered a multifunctional material, with a very important role not only in protection and lubrication but also in respiration, ionic and osmotic regulation, feeding, etc. (Yan et al, 2022;Seo et al, 2021). Most research studies have shown that the antifouling activity of this natural epidermal hydrogel secreted by fish is due to the presence of a group of antimicrobial polypeptides, with amphipathic-helical structures, which by their nature can interact strongly with the phospholipid membranes of microorganisms (Liu et al, 2023).…”
Section: Bioactive Compounds Based On Natural Designs For Antifouling...mentioning
confidence: 99%
“…Due to the exible deformation of loach's body, tiny scale distribution on the body surface, and the mucus retained on the scales, the DR performance of the loach is maximized. 25,26 Although the microstructure of the loach body surface triggers inspiration for the design of the bionic surface and has achieved some positive results on DR and anti-fouling, [27][28][29] further in-depth analysis on DR mechanisms is required and preparation of large-area microstructure for application is a challenge as well. In this study, the scale morphology of the loach was described, and the most appropriate structural characteristic parameters were selected.…”
Section: Introductionmentioning
confidence: 99%